2005
DOI: 10.1007/s11926-005-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of systemic vasculitis

Abstract: The systemic vasculitides are heterogeneous conditions of unknown etiology characterized by inflammation and necrosis of different sized blood vessels. Wegener's Granulomatosis, microscopic polyangiitis, and Churg Strauss syndrome are associated with anti-neutrophil cytoplasmic antibodies and affect small and medium blood vessels. They are very rare in childhood and peak in the 65 to 70 year old age group. Wegener's Granulomatosis appears to be more common in the North of Europe compared with the South. All ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 39 publications
2
54
0
6
Order By: Relevance
“…Systemic vasculitis comprises a heterogeneous group of diseases characterized by a common histopathologic feature of inflammation and necrosis of blood vessels (41). Studies from England, Spain, and Scandinavia have shown that the overall annual incidence of primary systemic vasculitis is approximately 20 cases per million (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic vasculitis comprises a heterogeneous group of diseases characterized by a common histopathologic feature of inflammation and necrosis of blood vessels (41). Studies from England, Spain, and Scandinavia have shown that the overall annual incidence of primary systemic vasculitis is approximately 20 cases per million (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the true return rate is likely to be significantly higher than the above figure. In addition, when considering such a rare condition as Wegener's granulomatosis (UK incidence of 10.2/million/year and prevalence of 25/100 000), 12 our sample size of 199 Wegener's granulomatosis patients would, by extrapolation, be comparable to a sample group of 30 000 patients in a study of nasal polyps (prevalence of 4.2 per cent of adult population). 13 …”
Section: Discussionmentioning
confidence: 99%
“…9,10 Over the years, the frequency of HBV infection, and thus associated PAN, has come down due to screening of blood products before transfusion and increasing vaccination. 11,12 The frequency of HBV associated PAN amongst all patients of the French vasculitis group (FVG) has come down from a high of 48.8% in five years (1982)(1983)(1984)(1985)(1986)) to 17.4% in six years (1997)(1998)(1999)(2000)(2001)(2002). 11,13 HBsAntigen and anti-HBs antibody immune complexes have been demonstrated in the vascular lesions in these patients.…”
Section: Incidencementioning
confidence: 99%